Post-partum uterine prolapse in a doe - SELVARAJU, M; VIJAYANAND, K R; PARTHIBAN, R; VIJAY, D; JAGATHEESAN, P N RICHARD (The Indian Journal of Animal Reproduction, 2023)
A case of uterine prolapse and its management in a non-descript doe has been reported.
Keywords: Uterine prolapse; doe; post-partum